MODELS OF COMMUNICATIVE COMPETENCE IN TEACHING FOREIGN LANGUAGE (Journal of Universal Science Research, 2024)
In this article is devoted to the explore the term communicative competence in a foreign language. It goes through the various definitions and some models of the communicative competence especially those most common models of Hymes and Canale and Swain and Alcon. It shows how the term ‘communicative competence’ has come into existence during the 1970s and how it has become a major aim for teaching and learning of English as a foreign language in many countries.